Comprensión lectora en estudiantes del sector urbano y rural - Yugcha Usuño, Jissela Anahi (2025)
The present study, entitled “Reading Comprehension in Students from Urban and Rural Areas,” aimed to determine the levels of reading comprehension and the socioeconomic factors that characterize students from urban and rural sectors of the Ambato canton. Methodologically, the research adopted a quantitative approach with a non-experimental, basic, descriptive, field-based, and cross-sectional design. The study was conducted with a sample of 56 first-year high school students (BGU) from class “A” at the “Teresa Flor” Educational Unit, located in La Merced parish (urban area), and from the “César Augusto Salazar Chávez” Educational Unit, located in Atahualpa parish (rural area) of the city. For data collection, a reading comprehension test and a socioeconomic survey were administered. The results revealed that, at the literal level, students from the urban sector demonstrated higher performance compared to their rural peers. At the inferential level, most students from both sectors showed limited development in text analysis and inference. Finally, at the critical level, both groups exhibited weaknesses in reflection, deep analysis, and the formulation of critical judgments about the content of a text. Regarding socioeconomic factors, significant contrasts were identified: for instance, mothers from the urban sector tended to work in commerce-related activities, while those from the rural sector were mainly engaged in sewing and agricultural work, among other findings.